1995
DOI: 10.1007/bf00240958
|View full text |Cite
|
Sign up to set email alerts
|

Cyclophosphamide cystitis as a model of visceral pain in rats: model elaboration and spinal structures involved as revealed by the expression of c-Fos and Krox-24 proteins

Abstract: The evoked expression of the immediate early gene (IEG)-encoded proteins c-Fos and Krox-24 was used to monitor spinal visceronociceptive processing that results from cyclophosphamide cystitis in behaving rats. Animals received a single dose of 100 mg/kg i.p. of cyclophosphamide and survived for 30 min to 5 h. Longer survival times were not considered because of ethical considerations. Cyclophosphamide-injected animals developed characteristic behavioral signs in parallel with development of bladder lesions and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
80
1
1

Year Published

1997
1997
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(86 citation statements)
references
References 82 publications
4
80
1
1
Order By: Relevance
“…In contrast, increases in PGD 2 in the urinary bladder were biphasic, occurring with both acute (4 h) and chronic CYP treatment but not acute (48 h) treatment (14). Animal studies have also indicated that CYP treatment (acute treatment) in the rat induces increased frequency of voiding in awake rats and urinary bladder hyperreflexia in anesthetized rats (14,(21)(22)(23)26), and these changes are maintained with acute (48 h) and chronic CYP treatment. Thus CYP treatment represents a noxious, chemical irritation of the urinary bladder that also induces bladder overactivity.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, increases in PGD 2 in the urinary bladder were biphasic, occurring with both acute (4 h) and chronic CYP treatment but not acute (48 h) treatment (14). Animal studies have also indicated that CYP treatment (acute treatment) in the rat induces increased frequency of voiding in awake rats and urinary bladder hyperreflexia in anesthetized rats (14,(21)(22)(23)26), and these changes are maintained with acute (48 h) and chronic CYP treatment. Thus CYP treatment represents a noxious, chemical irritation of the urinary bladder that also induces bladder overactivity.…”
Section: Discussionmentioning
confidence: 99%
“…In the present report, we used a well-established model of urinary bladder inflammation (Bon et al 1997(Bon et al , 2003Lanteri-Minet et al 1995) to examine the consequences of inflammation on characteristics of TL and LS bladder neurons in the rat, focusing on their sensitivity to purinergic receptor agonists. We hypothesized that changes in the excitability and sensitivity of bladder sensory neurons to endogenous purinergic receptor agonists contribute to bladder dysfunction, discomfort, and pain that characterize bladder disorders such as cystitis.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies involving a chemically (cyclophosphamide; CYP)-induced bladder inflammation (Cox, 1979;Maggi et al, 1992;Lantéri-Minet et al, 1995;Vizzard, 2000a;Vizzard, 2000d;Zvarova and Vizzard, 2006) model have demonstrated alterations in neurochemical (Vizzard, 2000a;Vizzard, 2000dVizzard, , 2001Zvarova and Vizzard, 2006), electrophysiological (Jennings and Vizzard, 1999;Yoshimura and de Groat, 1999), organizational (Vizzard and Boyle, 1999;Vizzard, 2000b) and functional properties of bladder afferent neurons in dorsal root ganglia (DRG) and in central reflex micturition pathways as well as changes in the urinary bladder (xx). Neurotrophins, including nerve growth factor (NGF) have been implicated in mediating some of these changes.…”
Section: Introductionmentioning
confidence: 99%